Identification of a major QTL for adult plant resistance to coffee leaf rust (Hemileia vastatrix) in the natural Timor hybrid (Coffea arabica x C. canephora). Issue 1 (5th December 2013) - Romero, Gladys; Vásquez, Luisa M.; Lashermes, Philippe; Herrera, Juan C.; Debener, T.
Abstract Most of the commercial varieties of coffee (Coffea arabica L.) derived from the Timor hybrid (TH) have been shown to contain major genes for coffee leaf rust (CLR) resistance. To identify markers tightly linked to such genes, an F2 mapping population derived from a cross between 'Caturra' (susceptible variety) and the TH‐derived DI.200 line (highly resistant) was generated. Using expressed sequence information and a bioinformatics approach, both targeted region amplified polymorphism (TRAPs) markers and simple sequence repeat (SSR) markers were identified. Phenotypic evaluations in the field and under controlled conditions confirmed the existence of one quantitative trait locus for CLR resistance. Four candidate SSR markers were associated with high CLR resistance. They spanning a region of 2.5 cM designated QCLR_4 located within chromosome 4 of the international C. canephora map. The presence of this region was confirmed in a set of elite lines and commercial varieties. The QCLR_4 region corresponds to a new and genetically independent SH locus that could potentially be useful in gene pyramiding with other genes to enhance rust resistance in TH derivatives.